Birds of Periyar Tiger Reserve, Kerala, South India - Srivastava, K. K.; Zacharias, V. J.; Bhardwaj, A. K.; Mohammedjafer, P. (Indian Forester, 1993)
A checklist of birds of Periyar Tiger Reserve was prepared. Two hundred and fortynine species of birds are recorded in the reserve. Sixty species are new records for Periyar while 3 are new records for Kerala. The lesser number of wetland birds may be due the absence of marshes and shallow water areas in the Lake. Rarity of larger birds of prey may be due to their low population in nature or the agricultural practices in the surrounding areas. This study shows that Periyar has great potential for detailed orinithological research.